Remaining useful life prediction of crude oil pipeline by means of deterioration curves - Shaik, N.B. (John Wiley and Sons Inc., 2020)
Pipelines sometimes generate different kinds of environmental damages which are irreparable and hazardous due to various reasons such as natural hazards, external loads, and corrosion. Many soft computational methods have been introduced to assess the failure rates of pipelines since decades. However, the majority of studies were limited to specific conditions. The aim of this paper is to predict the remaining useful life of the crude oil pipeline by generating the deteriorating curves. The historical inspection data have been used to calculate the metal loss (ML) growth rates. ML anomalies were found to be a major effect on the deterioration rate of a crude oil pipeline. Deterioration curves were developed using ML growth rates on a timely basis. The results may help pipeline technicians in decision making for overhaul planning and to take essential arrangements or to repair when needed, so that produce losses of oil and gas industries can be reduced and hence the lifespan of a pipeline can be increased. Â© 2019 American Institute of Chemical Engineers